Method for optimizing pore structure of ZIF-8 derived monatomic catalyst based on'carrier gas flow velocity-humidity-zinc volatilization 'coupling response and application

By adjusting the inert carrier gas flow rate to control the humidity in the furnace and zinc volatility, the pore structure of ZIF-8-derived single-atom catalyst is optimized, and the existing methods are complex and cost-effective, achieving efficient and economical pollutant degradation effect.

CN120550846APending Publication Date: 2025-08-29TONGJI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510684748.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The existing single-atom catalyst pore control methods are complex and costly, making it difficult to achieve large-scale synthesis, and the existing methods are not conducive to optimizing the pore structure of the catalyst to improve catalytic activity.

Method used

By adjusting the inert carrier gas flow rate, the furnace humidity during the pyrolysis process is controlled, and the pore structure of ZIF-8-derived single-atom catalyst is optimized using zinc volatility to form a rich mesoporous structure, using a simple method without additional operational steps.

Benefits of technology

It significantly improves the specific surface area and mesoporous proportion of single-atom catalysts, achieves rapid degradation of pollutants, reduces preparation costs, facilitates large-scale production, and maintains high-efficiency pollutant removal capabilities under low concentrations of oxidants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120550846A_ABST
    Figure CN120550846A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of monatomic material preparation and advanced oxidation application, and particularly discloses a method for optimizing a ZIF-8 derived monatomic catalyst pore structure based on'carrier gas flow rate-furnace humidity-zinc volatilization 'coupling response and application. A ZIF-8 precursor is placed in a tubular furnace to be pyrolyzed, the humidity in the furnace is controlled by adjusting the flow rate of inert carrier gas, so that the content of zinc nanoparticles generated in situ in the material is influenced, the volatilization amount of zinc is further adjusted and controlled, and finally materials with different specific surface areas and mesoporous and microporous structures are obtained. Experimental results show that when the flow rate of carrier gas is reduced to 10 mL / min, the pore structure distribution and adsorption catalysis synergistic performance of the material reach the optimal state, and rapid Fenton-like degradation of organic pollutants can be promoted. The method is simple and convenient in process and environment-friendly, can complete pore structure optimization only by adjusting the flow velocity of the carrier gas without changing other reaction conditions, is suitable for large-scale preparation, and has a remarkable application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of single-atom material preparation and advanced oxidation application, and specifically relates to a method and application for optimizing the pore structure of ZIF-8 derived single-atom catalyst based on the coupled response of "carrier gas flow rate-furnace humidity-zinc volatilization". Background Art

[0002] Single-atom catalysts (SACs) have the characteristics of high metal atom utilization efficiency and adjustable electronic structure. They show high activity and high selectivity in the catalytic reaction process and can achieve efficient removal of target pollutants in a short time. Therefore, they have great application potential in the field of water treatment. In order to further improve the catalytic activity of single-atom catalysts, pore control technology can be used to optimize the support pore structure to enhance the single-atom catalytic performance. Existing single-atom catalyst pore control methods generally use template etching methods, which have complex preparation processes, high costs, and are not conducive to large-scale synthesis. Therefore, it is urgent to develop a simple, green, and economical in situ pore control strategy for single-atom catalysts. Summary of the Invention

[0003] In response to the above problems, the present invention provides a method and application for optimizing the pore structure of ZIF-8-derived single-atom catalysts based on the coupled response of "carrier gas flow rate-furnace humidity-zinc volatilization". This method can directionally change the pore structure of the catalyst through simple regulation of the inert carrier gas flow rate. A single-atom catalyst with the largest pore structure and the largest proportion of mesopores can be directionally obtained by using a low inert carrier gas flow rate. This catalyst can efficiently catalyze PMS and achieve rapid degradation of organic pollutants in the water environment. This regulation method only requires changing the inert carrier gas flow rate and does not require additional complex operating steps. It is simple and green, can be used for large-scale production, and has great application potential.

[0004] In order to achieve the above object, the technical solution of the present invention is as follows:

[0005] The present invention provides a method for optimizing the pore structure of a ZIF-8-derived single-atom catalyst based on a coupled response of "carrier gas flow rate-humidity-zinc volatilization", the method comprising the following steps:

[0006] S1: Weigh metal M salt and zinc nitrate hexahydrate, dissolve them in solvent to prepare solution A, and weigh dimethylimidazole and add it to solvent to prepare solution B; pour solution B into solution A, stir and react at room temperature, and obtain metal M-doped ZIF-8 precursor after centrifugation, washing, and vacuum drying, named M-ZIF-8;

[0007] S2: The M-ZIF-8 precursor in step S1 is placed on a porcelain boat in a quartz tube in a tubular furnace for pyrolysis. During the pyrolysis process, an inert gas is introduced at a flow rate of 10-40 mL / min. At the same time, the appropriate programmed temperature is adjusted as needed to ensure that the inert carrier gas has sufficient time to discharge water vapor from the tail end of the quartz tube during the pyrolysis process, thereby obtaining the M-ZIF-8-derived single-atom catalyst M-N3C1; as the inert gas flow rate decreases, the humidity in the tube increases, resulting in an increase in the water vapor content in the tube, which in turn leads to an increase in the content of ZnO nanoparticles generated by the reaction of zinc ions on M-ZIF-8 with water vapor in the tube, and further leads to an increase in the content of Zn nanoparticles generated by in situ carbon thermal reduction of ZnO nanoparticles during the heating process; ultimately, the amount of zinc volatilized in M-ZIF-8 at the pyrolysis temperature increases. The more zinc volatilizes, the richer the pore structure on the obtained single-atom catalyst, the more mesoporous structures are formed, and the larger the proportion of mesopores, thereby achieving the purpose of optimizing the pore structure of the ZIF-8-derived single-atom catalyst.

[0008] Furthermore, the heating program is as follows: in the first stage, the temperature is increased from 35°C to 45°C at a heating rate of 0.067°C / min; in the second stage, the temperature is increased from 45°C to 100°C at a heating rate of 2°C / min; in the third stage, the temperature is increased from 100°C to 950°C at a heating rate of 5°C / min. When the temperature is increased to 600°C, the relative humidity in the tube is 15%-18%. When the temperature is increased to 950°C, the temperature is maintained at 950°C for pyrolysis for 180 minutes, and finally naturally cooled from 950°C to room temperature to obtain the ZIF-8 derived single atom catalyst. The programmed temperature can be adjusted according to actual conditions, the purpose of which is to ensure that the inert carrier gas introduced has sufficient time to expel water vapor to reduce the humidity in the tube to the required value.

[0009] In step S1, the metal M salt is any one of cobalt nitrate hexahydrate, copper nitrate trihydrate and ferric nitrate nonahydrate.

[0010] Furthermore, in step S1, the solvent is any one of methanol, ethanol, and water, and the reaction is stirred at room temperature for 24 hours. The product is washed with methanol 3-6 times and dried in vacuum at 60-80°C for 8-12 hours to obtain M-ZIF-8, which contains 27.5-28wt% of Zn.

[0011] Furthermore, the inert carrier gas is nitrogen or argon;

[0012] The introduction of an inert carrier gas can change the water vapor content, i.e., humidity, in the tube by continuously discharging the gas in the tube. Therefore, the humidity in the tube can be controlled by adjusting the inert carrier gas flow rate. The lower the inert carrier gas flow rate, the less water vapor can be discharged, the greater the humidity in the tube, and the higher the water vapor content in the tube. During the pyrolysis process of M-ZIF-8, when the pyrolysis temperature reaches 400-600°C, the zinc ions on M-ZIF-8 react with water vapor to generate ZnO nanoparticles. Therefore, the humidity in the tube determines the content of ZnO nanoparticles generated on M-ZIF-8. As the pyrolysis temperature continues to rise to 600-700°C, the ZnO nanoparticles generated on M-ZIF-8 will be converted into Zn nanoparticles through carbon thermal reduction. Therefore, the content of ZnO nanoparticles determines the content of Zn nanoparticles generated by the conversion. As the pyrolysis temperature continues to rise to 950°C, a large amount of zinc on M-ZIF-8 volatilizes. The content of Zn nanoparticles generated at 600-700°C determines the amount of zinc volatilized from M-ZIF-8 after pyrolysis at 950°C. The higher the Zn nanoparticle content, the greater the amount of zinc volatilization. Zinc volatilization has a pore-forming effect on the material. The more zinc volatilizes, the richer the pore structure on the obtained single-atom catalyst, the more mesoporous structures are formed, and the greater the proportion of mesopores. Therefore, the specific surface area, micropore and mesopore structure, and mesopore proportion of the single-atom catalyst can be in situ and directionally controlled by coupling the "carrier gas flow rate-furnace humidity-zinc volatilization" mechanism. Among them, the carrier gas flow rate is the inducing factor, and the regulation of the material's pore structure by zinc volatilization is the ultimate result.

[0013] The above technical solution explains how the inert carrier gas flow rate affects humidity, changes the amount of Zn volatilization, and ultimately regulates the core of the pore structure and its impact. The original humidity in the quartz tube in the tubular furnace is about 70%. After the inert carrier gas is introduced, the carrier gas will continuously discharge the gas in the tube. The discharge of water vapor will cause the humidity in the quartz tube to gradually decrease. Different carrier gas flow rates will cause the humidity in the quartz tube in the tubular furnace to be different at the same time. When the carrier gas flow rate reaches 180mL / min and the furnace temperature reaches 600℃, the humidity in the tube is 9.3%. When the carrier gas flow rate is reduced to 10mL / min, the humidity in the tube increases to 18.0%, indicating that the reduction in the carrier gas flow rate will cause the water vapor content in the tube to increase significantly. This will result in different contents of ZnO nanoparticles generated by the reaction of zinc ions on M-ZIF-8 with water vapor in the tube when the temperature reaches 600°C. The lower the inert carrier gas flow rate, the more ZnO nanoparticles are generated. This will further lead to different contents of Zn nanoparticles generated by in situ carbon thermal reduction of ZnO nanoparticles during the programmed temperature rise from 600 to 700°C. The lower the inert carrier gas flow rate, the more Zn nanoparticles are generated by the conversion. This will in turn lead to significantly different amounts of zinc volatilization on M-ZIF-8 under 950°C conditions. As the carrier gas flow rate decreases from 180 mL / min to 10 mL / min, the amount of Zn volatilized on the material increases from about 79% to 96.4%. The lower the inert carrier gas flow rate, the greater the amount of zinc volatilization. Different volatilization amounts of zinc on M-ZIF-8 will cause the prepared M-N3C1 to have different specific surface areas, mesopore and micropore structures. The lower the inert carrier gas flow rate, the larger the specific surface area of ​​M-N3C1, the richer the pore structure, and the larger the proportion of mesopores, thus realizing the directional regulation of the pore structure of single-atom catalysts.

[0014] In the M-N3C1 catalyst, the active metal M is any one of the transition metals Co, Cu, and Fe, and the metal loading is 0.3-2.1 wt%. As the inert carrier gas flow rate decreases, the Zn content on the single-atom catalyst decreases, and the BET specific surface area, mesopore area and volume, and average pore size of the catalyst increase regularly. Taking the Co-N3C1 catalyst as an example, when the carrier gas flow rate decreases from 180 mL / min to 10 mL / min, the BET specific surface area and mesopore area of ​​the catalyst increase from 940.4 m 2 / g and 42.55m 2 / g increased to 1243.5m 2 / g and 112.7m 2 / g, the micropore volume and mesopore volume of the catalyst are from 0.38cm 3 / g and 0.035cm 3 / g increased to 0.59cm 3 / g and 0.096cm 3 / g, the mesopore ratio increased from 8.52% to 15.41%, and the average pore diameter increased from 1.74nm to 2.03nm. Experimental results show that the M-N3C1 prepared at an inert carrier gas flow rate of 10mL / min has the largest specific surface area, the richest pore structure, the highest mesopore ratio, and the best pore structure.

[0015] The present invention also provides the use of the aforementioned M-N3C1 in activating PMS to degrade organic pollutants in water. When the inert carrier gas flow rate is optimized to 10 mL / min, the resulting M-N3C1 achieves optimal pollutant removal. With the addition of 0.04 g / L catalyst and 0.712 mmol / L PMS, M-N3C1 efficiently adsorbs bisphenol A (BPA). Simultaneously, the M single atoms on the M-N3C1 effectively activate PMS, achieving rapid removal and complete degradation of 10 mg / L BPA within 5 minutes.

[0016] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0017] 1. The pore control measures of the single-atom catalyst in this invention utilize the high-temperature volatilization properties of Zn in ZIF-8 derivative materials. By reducing the inert carrier gas flow rate to increase the humidity within the quartz tube in the tubular furnace during pyrolysis, the volatilization of Zn from ZIF-8 is increased, thereby increasing the micropore and mesoporous structure of the single-atom catalyst and significantly increasing the proportion of mesopores. This control method does not require the introduction of additional reagents and templates, nor does it require acid-base etching. The control method is simple, green, easy to operate, low in preparation cost, and convenient for large-scale production.

[0018] 2. The ZIF-8-derived single-atom catalyst with optimized mesopore structure in the present invention accelerates the transfer rate of pollutants and oxidants, promotes the enrichment of pollutants and PMS on the material, and achieves rapid (within 5 minutes) and complete degradation of pollutants.

[0019] 3. The ZIF-8-derived single-atom catalyst, with its optimized pore structure, accelerates the migration and accumulation of pollutants and PMS on the single-atom material, achieving complete degradation of pollutants at a low PMS concentration (0.3 mmol / L). Furthermore, thanks to the protection of its pore structure, the single-atom material is relatively stable and maintains high pollutant removal efficiency in real-world water environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 X-ray diffraction patterns of Co-ZIF-8 and Co-N3C1 series catalysts.

[0021] Figure 2 The morphology of Co-N3C1-10, where a is a scanning electron microscope (SEM) image; b is a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) image.

[0022] Figure 3 are X-ray absorption fine structure spectra, where a is the X-ray absorption near-edge structure spectrum; b is the extended X-ray absorption fine structure; and c is the extended X-ray absorption fine structure and fitting spectrum of Co-N3C1-10.

[0023] Figure 4 The humidity difference inside the quartz tube in the tube furnace at 600℃ under different nitrogen flow rates.

[0024] Figure 5 Transmission electron microscopy images of the catalysts prepared by pyrolysis at 600°C and 700°C under different nitrogen flow rates (the generated ZnO nanoparticles and Zn nanoparticles can be clearly observed in the TEM image).

[0025] Figure 6 is the residual Zn content in the material during the pyrolysis of Co-ZIF-8.

[0026] Figure 7 Schematic diagram of the formation of the material's pore structure regulated by nitrogen flow rate during the pyrolysis of Co-ZIF-8.

[0027] Figure 8 These are the nitrogen adsorption and desorption curves of the Co-N3C1 series catalysts prepared at different nitrogen flow rates.

[0028] Figure 9 The pore size distribution diagrams of micropores and mesopores in the Co-N3C1 series catalysts prepared under different nitrogen flow rates, where a is the micropore size distribution diagram; b is the mesopore size distribution diagram.

[0029] Figure 10 These are the effects of BPA adsorption and BPA degradation by activated PMS of the Co-N3C1 series materials prepared at different nitrogen flow rates, where a is the effect of BPA adsorption by Co-N3C1; b is the ultra-high performance liquid chromatogram of the desorption liquid of the material after adsorption; c is the effect of BPA degradation by activated PMS; d is the ultra-high performance liquid chromatogram of the desorption liquid of the material after degradation.

[0030] Figure 11 This is a diagram showing the effect of Co-N3C1-10 activating PMS to degrade BPA of different concentrations.

[0031] Figure 12 This is a diagram showing the effect of Co-N3C1-10 activating PMS to degrade BPA in actual water distribution.

[0032] Figure 13The characterization and removal effect diagram of the Cu-N3C1 series catalysts prepared under different nitrogen flow rates, where a is the X-ray diffraction pattern; b is the effect diagram of activated PMS degrading BPA; c is the ultra-high performance liquid chromatography diagram of the desorption liquid of the degraded material.

[0033] Figure 14 The characterization and removal effect diagram of the Fe-N3C1 series catalysts prepared under different nitrogen flow rates, where a is the X-ray diffraction pattern; b is the effect diagram of activated PMS degrading BPA; c is the ultra-high performance liquid chromatography diagram of the desorption liquid of the degraded material. DETAILED DESCRIPTION

[0034] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more apparent, the present invention is described clearly and completely below with reference to the accompanying drawings and specific examples. Where specific conditions are not specified in the examples, conventional conditions or those recommended by the manufacturer were used. Unless otherwise specified, the chemical reagents and instruments used were commercially available conventional products.

[0035] Example 1

[0036] This embodiment provides a method for optimizing the pore structure of a cobalt single-atom catalyst based on the coupled response of “carrier gas flow rate-furnace humidity-zinc volatilization”:

[0037] (1) Weigh zinc nitrate hexahydrate (8 mmol) and cobalt nitrate hexahydrate (0.8 mmol) into a beaker, add 60 mL of methanol, and sonicate for 10 min to dissolve. This solution is named Solution A.

[0038] (2) Weigh 2-methylimidazole (32 mmol) into a beaker, add 40 mL of methanol, and sonicate for 10 min to dissolve the solution. This solution is named Solution B.

[0039] (3) Place solution A on a magnetic stirrer and stir vigorously. Pour solution B slowly and evenly into it and stir at room temperature for 24 h.

[0040] (4) The reaction solution was centrifuged (6000 r / min, 5 min), the supernatant was removed, the solid was collected, and then washed with methanol three times (35 mL each time). The washed solid was placed in a vacuum drying oven and dried at 60°C for 12 h to obtain a purple Co-doped solid powder, i.e., ZIF-8 precursor, named Co-ZIF-8. The ZIF-8 precursor contained 27.58 wt% Zn by inductively coupled plasma optical emission spectrometry (ICP-OES).

[0041] (5) After grinding Co-ZIF-8, 0.45 g was weighed into a porcelain boat and placed in the middle section of a quartz tube in a tubular furnace. The size of the quartz tube was 58 mm (inner diameter) × 1000 mm (length). The temperature program of the tubular furnace was controlled as follows: from 35°C to 45°C at a rate of 0.067°C / min, then from 45°C to 100°C at a rate of 2°C / min, and finally from 100°C to 950°C at a rate of 5°C / min. After pyrolysis at 950°C for 3 h, it was naturally cooled to obtain a Co single-atom catalyst (Co-N3C1) with 3 N and 1 C coordination. While the temperature was programmed, nitrogen was introduced at a certain rate into the front end of the quartz tube. During the pyrolysis process, the nitrogen would carry the air in the quartz tube in the tube furnace through the pipeline and be discharged from the tail end of the quartz tube. By changing the flow rate of nitrogen introduced during the pyrolysis process (180 mL / min, 130 mL / min, 100 mL / min, 70 mL / min, 40 mL / min and 10 mL / min), Co-N3C1 with different pore structures was prepared and named Co-N3C1-180, Co-N3C1-130, Co-N3C1-100, Co-N3C1-70, Co-N3C1-40 and Co-N3C1-10 respectively.

[0042] (6) X-ray diffraction patterns (XRD, Figure 1 ), which shows that Co on the Co-N3C1 series materials is likely to exist in the form of single atoms, and there is no obvious difference in the XRD patterns of the Co-N3C1 series catalysts prepared under different nitrogen flow rates.

[0043] (7) Taking Co-N3C1-10 as an example, its SEM spectrum and HAADF-STEM spectrum ( Figure 2 Figures a and b) show that the Co-N3Cl2 has a regular dodecahedral structure with a size of 200-500 nm. Furthermore, it was confirmed that Co is uniformly distributed on the carbon material in a single-atom form. The Co content in the Co-N3Cl2-10 material was determined to be 2.1 wt% by ICP-OES.

[0044] (8) With the help of synchrotron radiation, the X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) of the material were recorded. Figure 3 As shown in Figure a, XANES shows that the chemical valence state of Co is between 0 and +2. Figure 3 As shown in b and c, EXAFS confirmed that there was no significant difference in the existence form of Co in the metal center of the Co-N3C1 series catalysts prepared at different nitrogen flow rates. They all existed in the form of single atoms, and the coordination number of N around the metal center Co was 3, and the coordination number of C was 1.

[0045] (9) During the pyrolysis of Co-ZIF-8, the front and rear ends of the quartz tube in the tube furnace were not in the heating area. Therefore, the humidity inside the quartz tube was detected by a hygrometer at the rear end of the quartz tube. It was found that when the temperature rose to 600 °C, the humidity inside the quartz tube changed as follows: Figure 4 As the nitrogen flow rate decreased from 180 mL / min to 10 mL / min, the humidity in the tube increased from 9.3% to 18% (the original humidity in the quartz tube was about 70%). Figure 5 The results showed that when the temperature rose to 600°C, ZnO nanoparticles were generated on the Co-ZIF-8 surface due to the reaction between zinc ions and water vapor. The amount of ZnO nanoparticles generated increased significantly as the nitrogen flow rate decreased from 180 mL / min to 10 mL / min. When the temperature was raised to 700°C, TEM results revealed that the ZnO nanoparticles generated at 600°C were converted into Zn nanoparticles through an in situ carbothermal reaction. The amount of ZnO nanoparticles generated determined the content of the converted Zn nanoparticles.

[0046] (10) Figure 6 The changes in Zn content in Co-ZIF-8 during pyrolysis at different nitrogen flow rates reveal that the Zn content in the material gradually decreases with increasing pyrolysis temperature, indicating that the Zn in Co-ZIF-8 is gradually volatilizing. When the nitrogen flow rate is 180 mL / min and the temperature rises to 950°C, the vast majority of the Zn volatilizes from the Co-ZIF-8, causing the Zn content in the material to decrease from 27.58 wt% to 5.83 wt%. Simultaneously, as the nitrogen flow rate decreases from 180 mL / min to 10 mL / min, the Zn content in the material decreases from 5.83 wt% to 1.65 wt%, meaning that the amount of Zn volatilized from the material increases from approximately 79% to 95%. Zn volatilization creates a portion of the pore structure for the Co single-atom catalyst. At this point, the greater the amount of Zn volatilization, the more pore structure is created. Specifically, the lower the nitrogen flow rate, the greater the humidity in the quartz tube, the more ZnO nanoparticles generated, the more Zn nanoparticles generated by ZnO conversion, the greater the Zn volatilization, the more pore structures formed on Co-N3C1, and the greater the proportion of mesopores. The detailed schematic diagram of the evolution of pore structure regulated by nitrogen flow rate is shown in the figure. Figure 7 shown.

[0047] (11) Results of nitrogen adsorption and desorption ( Figure 8 ) showed that as the nitrogen flow rate decreased from 180 mL / min to 10 mL / min, the specific surface area of ​​Co-N3C1 gradually increased, which was due to the increased micropore and mesoporous structure providing a richer specific surface area.

[0048] Micropore and mesopore pore size distribution diagram ( Figure 9) shows that the decrease in nitrogen flow rate will lead to a significant increase in the pore structure of Co-N3C1 with micropores in the range of 0.4-2nm and mesopores in the range of 2-10nm. The detailed data are listed in Table 1. The prepared Co-N3C1-180, Co-N3C1-70, Co-N3C1-40, and Co-N3C1-10 all have large specific surface areas, and with the decrease in nitrogen flow rate, the BET (Brunauer-Emmett-Teller) specific surface area (S BET ) from 940.4m 2 / g increased to 1243.5m 2 / g. The mesopore area and mesopore volume calculated by BJH (Barret-Joyner-Halenda) method were calculated from 42.5m 2 / g and 0.0353cm 3 / g increased to 112.7m 2 / g and 0.0957cm 3 / g, which is about three times the original volume. The micropore volume obtained by HK model (Horvath-Kawazoe) increased from 0.3847cm 3 / g increased to 0.5954cm 3 / g, among which the volume of micropores with a diameter of 0.9-2 nm is from 0.0783 cm 3 / g increased to 0.1666cm 3 / g, these micropores can adsorb small molecular organic pollutants through the pore filling effect. In addition, when the nitrogen flow rate is 180mL / min, 70mL / min, 40mL / min and 10mL / min, the proportion of Co-N3C1 mesopores is 8.52%, 8.51%, 11.8% and 15.41%, respectively. This shows that reducing the nitrogen flow rate to below 40mL / min can significantly increase the proportion of mesopores in the single-atom catalyst.

[0049] These results indicate that decreasing the nitrogen flow rate drives enhanced zinc volatilization from the material, resulting in a Co single-atom catalyst with a richer pore structure and a higher proportion of mesopores. Therefore, this coupled response mechanism of "carrier gas flow rate-furnace humidity-zinc volatilization" allows for targeted manipulation of the pore structure of Co single-atom catalysts.

[0050] Although according to the above conclusion, the lower the nitrogen flow rate, the richer the pore structure, it was found in the experiment that when the flow rate was lower than 10 mL / min, the humidity in the quartz tube was very high and the material yield was very low. About 0.45 g of precursor could only obtain 0.07 g of catalyst. It is speculated that Zn has basically volatilized and the structure of the material may have been destroyed. Therefore, the optimal nitrogen flow rate selected in this application is 10 mL / min.

[0051] Table 1 Preparation conditions, Zn content, specific surface area, pore volume and average pore size distribution of Co-N3C1 series catalysts

[0052]

[0053] (12) The effects of a series of Co-N3C1 adsorption and activation of PMS on the removal of BPA from water are as follows: Figure 10 As shown, where C is the concentration of BPA in the aqueous solution at the adsorption or degradation time, and C0 is the initial concentration of BPA in the aqueous solution.

[0054] Co-N3C1 catalyst (dosage 0.04 g / L) was added to a 10 mg / L BPA aqueous solution to conduct a BPA adsorption experiment at room temperature. Figure 10 In figure a), the results show that as the nitrogen flow rate decreases from 180mL / min to 10mL / min, the catalyst's ability to adsorb BPA is significantly improved thanks to the increase in the pore structure of Co-N3C1. Specifically, Co-N3C1-180 can only remove 7.2% of BPA after 60 minutes of adsorption. However, as the nitrogen flow rate decreases, the efficiency of BPA removal by the prepared Co-N3C1 is significantly improved. When the flow rate is reduced to 10mL / min, the prepared Co-N3C1-10 can adsorb and remove more than 80% of BPA. The optimization of the pore structure induced by nitrogen flow rate regulation not only improves the performance of BPA adsorption removal, but more importantly, this improvement in adsorption performance enhances the effect of Co-N3C1 in catalytic degradation of BPA.

[0055] According to the adsorption experiment results, for a 10 mg / L BPA aqueous solution, Co-N3C1 can reach BPA adsorption equilibrium within 30 minutes. Therefore, after BPA reaches adsorption equilibrium (30 minutes), PMS (PMS concentration in the solution is 0.712 mmol / L) is added to the reaction system to trigger the Co-N3C1 catalytic degradation of BPA at room temperature. The results are shown in Figure 2. Figure 10 As shown in Figure c, it can be seen that after the Co-N3C1 catalyst reaches adsorption equilibrium after 30 minutes of adsorption, the addition of PMS can further effectively degrade and remove BPA. As the nitrogen flow rate decreases from 180 mL / min to 10 mL / min, the ability of the prepared Co-N3C1 to catalyze PMS to degrade BPA is significantly enhanced. The BPA removal efficiency increases from approximately 20% (Co-N3C1-180) to 100% (Co-N3C1-10), and Co-N3C1-10 can achieve complete removal of BPA within 5 minutes.

[0056] Inductively coupled plasma-mass spectrometry (ICP-MS) detection found that the Co dissolution concentration in the solution was 22.8 μg / L after 30 minutes of degradation with Co-N3C1-10, indicating that there is basically no secondary risk caused by metal dissolution.

[0057] In addition, the adsorbed and degraded Co-N3C1 catalysts were collected by high-speed centrifugation, methanol solution was added to them and ultrasonicated for 60 minutes. According to the similarity-compatibility theory, the BPA adsorbed on the Co-N3C1 catalyst was desorbed and redissolved in the methanol solution. The methanol desorbate was then analyzed by ultra-high performance liquid chromatography. According to the strength of the characteristic peak representing BPA in the ultra-high performance liquid chromatography, it can be judged whether the BPA adsorbed on the Co-N3C1 catalyst was degraded. The results show that when the Co-N3C1 series catalysts only remove BPA by adsorption, the Co-N3C1 collected after the reaction desorbs a large amount of BPA with methanol ( Figure 10 b), and the BPA content desorbed from Co-N3C1-10 after the reaction was the highest, indicating that without the addition of PMS, Co-N3C1-10 adsorbed the pollutants on the surface and pores for removal; however, when the Co-N3C1 series catalysts were added with PMS to trigger the degradation reaction ( Figure 10 In (d), the BPA content detected in the methanol desorption solution of Co-N3C1 collected after the reaction was relatively low, and no BPA was detected in the desorption solution of Co-N3C1-10 after the reaction, indicating that the BPA adsorbed on Co-N3C1-10 would also be completely degraded, achieving ultra-fast degradation and removal of BPA.

[0058] (13) The initial concentration of BPA in the solution was modified from 10 mg / L to 2 and 5 mg / L respectively to explore the effect of the Co-N3C1-10 / PMS catalytic degradation system on the removal of BPA at different concentrations (the PMS concentration in the solution was 0.712 mmol / L, the catalyst dosage was 0.04 g / L, Figure 11 The results showed that the Co-N3C1-10 / PMS system could achieve complete degradation of BPA in a shorter time of 1 min.

[0059] (14) BPA was dissolved in tap water and river water to prepare a 10 mg / L BPA solution with the actual water environment as the background to explore the influence of complex background substances in the actual environment on the pollutant removal behavior. Figure 12The constructed Co-N3C1-10 / PMS catalytic degradation system maintained good catalytic degradation activity in real-world water bodies, including tap water and river water. When the Co-N3C1-10 material dosage was 0.04 g / L, the PMS concentration was 0.712 mmol / L, and the pollutant concentration was 10 mg / L, the Co-N3C1-10 activated the PMS and completely degraded BPA within 30 minutes, demonstrating excellent application potential.

[0060] Example 2

[0061] This example provides a method for optimizing the pore structure of a copper single-atom catalyst by coupling the response of carrier gas flow rate, furnace humidity, and zinc volatilization:

[0062] (1) Weigh a certain proportion of zinc nitrate hexahydrate (8 mmol) and copper nitrate trihydrate (0.8 mmol) into a beaker, add 60 mL of methanol, and sonicate for 10 min to dissolve. This solution is named Solution A.

[0063] (2) Weigh a certain amount of 2-methylimidazole (32 mmol) into a beaker, add 40 mL of methanol, and sonicate for 10 min to dissolve it. This solution is named Solution B.

[0064] (3) Place solution A on a magnetic stirrer and stir vigorously. Pour solution B slowly and evenly into it and stir at room temperature for 24 h.

[0065] (4) The reaction solution was centrifuged (6000 r / min, 5 min), the supernatant was removed, the solid was collected, and then washed with methanol three times (35 mL each time). The washed solid was placed in a vacuum drying oven and dried at 60°C for 12 h to obtain a reddish-brown Cu-doped solid powder, named Cu-ZIF-8; ICP-OES analysis showed that the Cu-ZIF-8 precursor contained 28 wt% Zn.

[0066] (5) After grinding Cu-ZIF-8, 0.45 g was weighed into a porcelain boat and placed in the middle of a quartz tube in a tubular furnace, and nitrogen was introduced at a certain rate. The temperature was raised from 35°C to 45°C at a rate of 0.067°C / min, then from 45°C to 100°C at a rate of 2°C / min, and finally from 100°C to 950°C at a rate of 5°C / min. After pyrolysis at 950°C for 3 h, it was naturally cooled to obtain a Cu single-atom catalyst (Cu-N3Cl) with 3 N and 1 C coordination. By changing the flow rate of nitrogen introduced during the pyrolysis process (180mL / min, 100mL / min, 70mL / min and 10mL / min), the humidity in the tube was changed during the pyrolysis process, thereby manipulating the volatilization behavior of Zn and regulating the pore structure. Cu-N3Cl with different pore structures were prepared and named Cu-N3C1-180, Cu-N3C1-100, Cu-N3C1-70, and Cu-N3C1-10, respectively.

[0067] (6) The XRD patterns of Cu-N3C1 series catalysts are similar to those of Co-N3C1 (e.g. Figure 13 Figure (a) shows that the Cu atoms on Cu-N3C1-180, Cu-N3C1-100, Cu-N3C1-70, and Cu-N3C1-10 also exist in single-atom form. ICP-OES analysis revealed that the Cu content on Cu-N3C1-10 is approximately 0.5 wt%.

[0068] (7) As the nitrogen flow rate decreased from 180 mL / min to 10 mL / min, the residual Zn content on Cu-ZIF-8 decreased from 5.12 wt% to 2.49 wt%, indicating that the volatilization of Zn increased from approximately 81.7% to 91.1%, thereby increasing the pore structure of the Cu-N3Cl catalyst. The Cu-N3Cl-10 prepared at the lowest nitrogen flow rate had the highest Zn volatilization content and the richest pore structure.

[0069] (8) The effects of a series of Cu single-atom catalysts on the adsorption and activation of PMS on the removal of BPA are as follows: Figure 13As shown in Figure 2b, when the dosage of the Cu-N3C1 series catalysts was 0.04 g / L, the BPA concentration was 10 mg / L, and the PMS dosage was 0.712 mmol / L, the results showed that Cu-N3C1-180, prepared at a high nitrogen flow rate, removed 28.2% of BPA by adsorption for 30 minutes. After the addition of PMS, catalytic degradation removed 33.6% of BPA. As the nitrogen flow rate decreased, the ability of the prepared Cu-N3C1 to remove BPA through both adsorption and catalytic degradation significantly increased. When the nitrogen flow rate was reduced to 10 mL / min, the prepared Cu-N3C1-10 directly removed 98.4% of BPA by adsorption, and after the addition of PMS, complete BPA removal was achieved within 10 minutes.

[0070] ICP-MS detection found that the Cu dissolution concentration in the solution was 33.7 μg / L after 30 minutes of degradation with Cu-N3C1-10, indicating that there was basically no secondary risk caused by metal dissolution.

[0071] The degraded Cu-N3C1-10 was collected, added with methanol solution and ultrasonicated for 60 min to obtain the desorption solution, and then the desorption solution was analyzed by ultra-high performance liquid chromatography to obtain the following Figure 13 The chromatogram shown in Figure (c) shows no characteristic BPA peaks detected in the methanol desorption solution, indicating that the large amount of BPA adsorbed on Cu-N3C1-10 can also be completely degraded by this method. These results demonstrate that the pore structure of the Cu-N3C1 series catalysts can be manipulated by coupling the "carrier gas flow rate-furnace humidity-zinc volatilization" response, enhancing the Cu-N3C1's ability to adsorb and catalyze PMS degradation.

[0072] Example 3

[0073] This embodiment provides a method for optimizing the pore structure of an iron single-atom catalyst by coupling the response of “carrier gas flow rate-furnace humidity-zinc volatilization”:

[0074] (1) Weigh a certain proportion of zinc nitrate hexahydrate (8 mmol) and ferric nitrate nonahydrate (0.8 mmol) into a beaker, add 60 mL of methanol, and sonicate for 10 min to dissolve. This is named solution A.

[0075] (2) Weigh a certain amount of 2-methylimidazole (112 mmol) into a beaker, add 70 mL of methanol, and sonicate for 10 min to dissolve it. This solution is named Solution B.

[0076] (3) Place solution A on a magnetic stirrer and stir vigorously. Pour solution B slowly and evenly into it and stir at room temperature for 24 h.

[0077] (4) The reaction solution was centrifuged (4000 r / min, 3 min), the supernatant was removed, the solid was collected, and 35 mL of methanol was added for ultrasonic washing for 3 minutes. The supernatant was removed by centrifugation (4000 r / min, 2-3 min). This washing was repeated 6 times to ensure that the supernatant was clear and transparent without dark brown solid. The product was placed in a vacuum drying oven and dried at 60 ° C for 12 h to obtain a light yellow Fe-doped solid powder, named Fe-ZIF-8. After ICP-OES analysis, the Fe-ZIF-8 precursor contained 27.5 wt% Zn.

[0078] (5) After grinding Fe-ZIF-8, 0.45 g was weighed into a porcelain boat and placed in the middle section of a quartz tube in a tubular furnace, and nitrogen was introduced at a certain rate. The temperature was raised from 35°C to 45°C at a rate of 0.067°C / min, then from 45°C to 100°C at a rate of 2°C / min, and finally from 100°C to 950°C at a rate of 5°C / min. After pyrolysis at 950°C for 3 h, the catalyst was naturally cooled to obtain an Fe single-atom catalyst (Fe-N3Cl) with three N and one C coordination groups. By changing the nitrogen flow rate during the pyrolysis process (180mL / min, 100mL / min, 70mL / min, 40mL / min and 10mL / min), the humidity in the tube was changed, and the volatilization behavior of Zn was manipulated to adjust the pore structure. Fe-N3Cl with different pore structures were prepared and named Fe-N3C1-180, Fe-N3C1-100, Fe-N3C1-70, Fe-N3C1-40 and Fe-N3C1-10, respectively.

[0079] (6) Figure 14 The XRD patterns of the Fe-N3C1 series catalysts, shown in Figure (a), are similar to those of the aforementioned Co-N3C1 and Cu-N3C1 catalysts, indicating that the active Fe sites on these catalysts also exist as single atoms. ICP-OES analysis reveals that the Fe content on Fe-N3C1-10 is approximately 0.5 wt%.

[0080] (7) The Zn contents of Fe-N3C1-180, Fe-N3C1-100, Fe-N3C1-70, Fe-N3C1-40, and Fe-N3C1-10 were 4.33 wt%, 3.3 wt%, 3.02 wt%, 1.48 wt%, and 1 wt%, respectively, indicating that as the nitrogen flow rate decreased from 180 mL / min to 10 mL / min, the Zn volatilization amount in Fe-ZIF-8 increased from approximately 84.3% to 96.4%, thereby increasing the pore structure of the Fe-N3C1 catalyst. Fe-N3C1-10 prepared at the lowest nitrogen flow rate had the largest Zn volatilization amount and the most pore structure.

[0081] (7) Figure 14 As shown in (b), when the dosage of the Fe-N3C1 series catalysts is 0.04 g / L, the BPA concentration is 10 mg / L, and the PMS dosage is 0.712 mmol / L, as the nitrogen flow rate decreases during the pyrolysis process, the ability of Fe-N3C1 to remove BPA by adsorption and activated PMS to remove BPA by degradation increases from 7.0% and 15.0% to 94.0% and 100%, respectively.

[0082] In addition, the degraded Fe-N3C1-10 was collected, added to methanol solution and ultrasonicated for 60 min to obtain the desorption solution, and then analyzed by ultra-performance liquid chromatography, it was found that no BPA characteristic peak was detected in the methanol desorption solution, such as Figure 14 As shown in Figure (c), the large amount of BPA adsorbed on Fe-N3Cl1-10 was completely degraded and removed. These results further demonstrate that the coupled response of carrier gas flow rate, furnace humidity, and zinc volatilization can regulate the pore structure of the Fe single-atom catalyst, enhancing the ability of Fe-N3Cl1 to adsorb and catalyze PMS degradation of pollutants.

[0083] The above examples demonstrate that by simply regulating the inert carrier gas flow rate during the pyrolysis process to change the humidity within the quartz tube in the tubular furnace and thereby controlling the volatilization of Zn, in situ optimization of the pore structure of the ZIF-8-derived single-atom catalyst was successfully achieved based on this simple coupled response regulation, significantly increasing the proportion of mesopores and thereby enhancing the ability of the single-atom catalyst to adsorb and degrade organic pollutants. This method only requires changing the inert carrier gas flow rate, is simple and green to operate, has a wide range of applicable metals, has low preparation costs, and can be mass-produced. The single-atom catalyst with optimized pore structure can efficiently adsorb organic pollutants and rapidly activate PMS to degrade organic pollutants, has strong anti-interference ability, and is essentially free of secondary pollution caused by metal dissolution, showing great application potential.

[0084] The above description of the examples is intended to facilitate understanding and use by those skilled in the art. Those skilled in the art will readily be able to make various modifications to these examples and apply the general principles described herein to other examples without requiring creative effort. Therefore, the present invention is not limited to the above examples. Improvements and modifications made by those skilled in the art based on the present invention, without departing from the principles of the present invention, should fall within the scope of the present invention.

Claims

1. A method for deriving the pore structure of a single-atom catalyst from ZIF-8 based on the coupled response of "carrier gas flow rate-humidity-zinc volatilization" comprises the following steps: S1: Weigh metal M salt and zinc nitrate hexahydrate, dissolve them in solvent to prepare solution A, and weigh dimethylimidazole and add it to solvent to prepare solution B; pour solution B into solution A, stir and react at room temperature, and obtain metal M-doped ZIF-8 precursor after centrifugation, washing, and vacuum drying, named M-ZIF-8; S2: The M-ZIF-8 obtained in step S1 is placed in a tubular furnace for pyrolysis to obtain the M-ZIF-8-derived single-atom catalyst M-N3C1. During the pyrolysis process, the pore structure of the ZIF-8-derived single-atom catalyst is optimized by the "carrier gas flow rate-humidity-zinc volatilization" coupled response. The pyrolysis process is specifically as follows: an inert gas is introduced into the tubular furnace at a flow rate of 10-40 mL / min, and the tubular furnace is heated according to a set heating program. During the heating process, the inert gas flow rate is maintained constant, and the air in the furnace is continuously discharged.

2. The method according to claim 1, characterized in that The heating program is as follows: in the first stage, the temperature is increased from 35°C to 45°C at a heating rate of 0.067°C / min; in the second stage, the temperature is increased from 45°C to 100°C at a heating rate of 2°C / min; in the third stage, the temperature is increased from 100°C to 950°C at a heating rate of 5°C / min, and when the temperature is increased to 600°C, the relative humidity in the furnace is 15%-18%. When the temperature is increased to 950°C, the temperature is maintained at 950°C for 180 minutes of thermal decomposition, and finally naturally cooled from 950°C to room temperature to obtain the ZIF-8 derived single atom catalyst.

3. The method according to claim 1, characterized in that During the pyrolysis process, when the temperature is between 400°C and 600°C, zinc ions in M-ZIF-8 react with water vapor to generate ZnO nanoparticles; when the temperature is between 600°C and 700°C, the ZnO nanoparticles are in situ carbon-thermally reduced to generate Zn nanoparticles; and when the temperature is 950°C, the zinc element in M-ZIF-8 volatilizes.

4. The method according to claim 1, wherein In step S1, the metal M salt is any one of cobalt nitrate hexahydrate, copper nitrate trihydrate and ferric nitrate nonahydrate.

5. The method according to claim 1, wherein The solvent is any one of methanol, ethanol, and water. The reaction is stirred at room temperature for 24 hours. The product is washed with methanol 3-6 times and dried in a vacuum at 60-80° C. for 8-12 hours to obtain M-ZIF-8, which contains 27.5-28 wt% of Zn.

6. The method according to claim 1, characterized in that The inert carrier gas is nitrogen or argon.

7. Use of the catalyst M-N3Cl obtained by the method according to any one of claims 1 to 6 in activating peroxymonosulfate (PMS) to degrade organic pollutants in water.

Citation Information

Cited By

  • A preparation method of a single-atom catalyst based on calcination atmosphere regulation of carrier types, a single-atom catalyst and application thereof

    CN122424849A